Electronic structure of aromatic monomolecular films: the effect of molecular spacers and interfacial dipoles - Kong, Lingmei; Chesneau, Frederick; Zhang, Zhengzheng; Staier, Florian; Terfort, Andreas; Dowben, P. A.; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2011)
The electronic structure of several arene-based monomolecular films on Au(111), with and without an alkyl linker between the aromatic unit and thiol headgroup, has been investigated by photoemission and inverse photoemission. While the HOMO-LUMO gap in these films was found to depend on the aromatic backbone, the molecular band offset of the electronic states was strongly affected by the interfacial dipole. The smallest HOMO-LUMO gap was found for the strongly conjugated anthracene moiety, intermediate for terphenyl, and widest for the perfluorinated terphenyl. The perfluorinated terphenyl-based films appear to be more n-type as a semiconductor than the terphenyl or anthracene-based monolayers, as indicated by the placement of the Fermi level (chemical potential) relative to the conduction or lowest molecular orbital band edge. Accordingly, the occupied electronic states related to the aromatic rings sink to greater binding energies, well below those for the alkyl linker, and thus for the perfluorinated terphenyl, the aromatic orbital contribution is not to the HOMO but the HOMO-1 orbital (one occupied molecular orbital away from the HOMO). This placement of the perfluorinated terphenyl aromatic orbital contribution is in drastic contrast to the nonfluorinated systems in our study, in which both HOMO and LUMO orbitals are extended throughout the aromatic moieties.
Gesehen am 06.07.2022